2001
DOI: 10.1097/00004691-200107000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation Effects on Language Function Depend on the Stimulation Parameters

Abstract: In previous studies it has been shown that picture-naming latencies can be facilitated with both suprathreshold single and repetitive transcranial magnetic stimulation (TMS/rTMS) over Wernicke's area. The aim of this study was to investigate whether low-frequency rTMS (1 Hz) or high-frequency rTMS (20 Hz) at subthreshold intensities is also capable of influencing picture naming. In 16 healthy right-hand male subjects, trains of 1 Hz or 20 Hz were applied over either Wernicke's area, Broca's area, or the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 20 publications
4
74
0
1
Order By: Relevance
“…High-frequency rTMS has been shown to improve cognitive performance (Little et al, 2000;Sparing et al, 2001;Martis et al, 2003;O'Connor et al, 2005), however, the underlying mechanisms have not been investigated. We contend that a possible explanation is through its effects on GABAergic inhibitory neurotransmission critical in both the generation and synchronization of oscillatory activity (Whittington et al, 1995;Wang and Buzsaki, 1996;Bartos et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-frequency rTMS has been shown to improve cognitive performance (Little et al, 2000;Sparing et al, 2001;Martis et al, 2003;O'Connor et al, 2005), however, the underlying mechanisms have not been investigated. We contend that a possible explanation is through its effects on GABAergic inhibitory neurotransmission critical in both the generation and synchronization of oscillatory activity (Whittington et al, 1995;Wang and Buzsaki, 1996;Bartos et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, high-frequency rTMS has been shown to improve language functions in healthy individuals (Sparing et al, 2001), as well as to improve different aspects of memory in major depressive disorder patients (Little et al, 2000;Martis et al, 2003;O'Connor et al, 2005). In addition, rTMS on the motor cortex has been shown to enhance GABA-mediated inhibitory neurotransmission in healthy individualsFthat is, Daskalakis et al (2006) reported a lengthening of the cortical silent period (CSP), a measure reflective of GABA Bmediated inhibitory neurotransmission (Ziemann et al, 1996) with increased stimulation frequency, which was maximal at 20 Hz (Daskalakis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies did not report any modification after 1 Hz rTMS on either motor or cognitive functions. Although naming latency is facilitated only immediately after Wernicke's area stimulation at a frequency of 20 Hz, trains of 1 Hz failed to influence naming latencies (Sparing et al, 2001), and single session of 1 Hz TMS over the right or the left prefrontal areas did not interfere with neuropsychological functioning in normal volunteers (Koren et al, 2001). Furthermore, 1 Hz rTMS used continuously for 2 min of right or left prefrontal cortex did not modify P300 latency whereas 20 Hz rTMS applied in three trains of 5 s duration of left prefrontal cortex reduced significantly P300 latency (Evers et al, 2001).…”
Section: Introductionmentioning
confidence: 85%
“…22,33,35,52,53,77 Furthermore, repetitive navigated TMS (rTMS) and nonnavigated TMS are able to localize cortical language function. 18,19,40,48,69,80 Its clinical applicability and correlation to DCS during awake surgery have repeatedly been shown as well. 36,37,51,68,75 Although rTMS language mapping has already experienced some improvement, 40 the standard for preoperative, noninvasive language mapping remains functional MRI (fMRI).…”
mentioning
confidence: 93%